PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN TLOGOSARI WETAN 01 SEMARANG: Penelitian Media Pembelajaran - Kunti Shouma Tsaniya; Olivia Zakkia Nafis; Frisca Eman Rosaifa; Susilo Tri Widodo; Nur Indah Wahyuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Boredom becomes common in the monotonous learning process. Especially in teacher-centered learning alone without any interesting innovations. Therefore, creativity and innovation are needed in driving away boredom and fostering interest in learning in students. With the existence of interesting learning media, it will certainly encourage students to be more enthusiastic in the learning process. The purpose of this study is to determine how much influence the use of wordwall media has on increasing student learning activity in grade IV pancasila education subjects SDN Tlogosari Wetan 01. The research method used in this study is quantitative experiment. This research was carried out during two meetings where in the first meeting it became a control class where in the first meeting researchers still used conventional learning and only used learning videos while in the second meeting became an experimental class, namely researchers using wordwall learning media. The results of research that have been conducted show an increase in student activeness by 55.56%. From these results, it indicates that the use of wordwall-based interactive media can increase student learning motivation effectively and significantly.